Biosynthesis of silver nanoparticles with antibacterial, antioxidant, anti-inflammatory properties and their burn wound healing efficacy - Bold, Bum-Erdene; Urnukhsaikhan, Enerelt; Mishig-Ochir, Tsogbadrakh (Frontiers in Chemistry, 2022)
The current study aims to develop a novel burn wound ointment consisting of sheep’s tail ointment loaded with AgNP. The AgNP in the ointment serves as an antibacterial, antioxidant and anti-inflammatory agent. The AgNP was developed via the biological method with the assistance of the medicinal plant Rhodiola rosea. The characterization of AgNP was assessed using UV-Vis spectroscopy, FTIR, Zeta Potential, XRD, PCCS, SEM, and EDX techniques. The formation of AgNP was confirmed by UV-Vis spectrum at the absorbance of 430 nm, and the biomolecules responsible for reducing and capping the AgNP were characterized by FTIR analysis. The stability of AgNP was determined with Zeta potential, which revealed a highly stable colloidal solution with a surface charge of -68.38±3.4 mV. The synthesized AgNP had a face-centered cubic structure with a crystallite size of 23 nm and average grain size of 67.5 nm. The SEM image showed a fairly monodisperse 20 nm-sized spherical-shaped AgNP. The synthesized AgNP contained high purity of the silver, and a low concentration of AgNP inhibited both Gram-positive and Gram-negative bacteria. Moreover, the scavenging activity of AgNP was investigated using DPPH and H2O2 scavenging assay, and the results revealed a dose-dependent antioxidant activity with the highest activity at a concentration of 450 µg/ml. Finally, the burn wound healing effect was evaluated by applying the AgNP-loaded ointment to the wound site of BALB/c mice. The in-vivo studies confirmed that AgNP-loaded ointment reduced the wound size, decreased the epidermis layer, and lowered mast cell migration compared to untreated burn wounds. And the synthesized AgNP regulated both pro-inflammatory and anti-inflammatory gene expression, thereby promoting burn wound closure on BALB/c mice. The developed AgNP-loaded ointment has the potential to be applied in the biomedical field.